Pengaruh Likuiditas Terhadap Harga Saham Dengan Profitabilitas Sebagai Variabel Moderasi - Budiharjo, Roy; Rujito, Rujito (Universitas Gorontalo, 2023)
This research was carried out to find out how the impact of liquidity on stock prices with profitability as a moderating variable in infrastructure companies listed on the Indonesia Stock Exchange from 2016 to 2020 is the population taken. Purposive sampling is the sampling method used. The survey data is taken from the 2016-2020 Indonesian Capital Market Index (ICMD). Statistical testing was carried out using the t-test and multiple linear regression analysis, which first tested the classical assumptions. The results of this study indicate that: liquidity has a negative effect on stock prices and profitability has a positive effect on stock prices while profitability is unable to moderate the relationship between liquidity and stock prices.